Effectiveness of behavioral modification techniques in children having intellectual disability: pre and post evaluation - Afzal, Samreen; Siddique, Irun; Dogar, Imtiaz Ahmad; Azeem, M Waqar (Journal of Pakistan Psychiatric Society, 2020)
Effectiveness of behavioral modification techniques in children having intellectual disability “Pre and post evaluation